Environmental, resident and bystander exposure from spraying applications with unmanned aerial vehicles equipped with flat-fan nozzles or rotary atomizers - Pierre-Henri Dubuis; Céline Villars-Corbex; M. Clare Butler Ellis; H. Christoph Geiser; Jeremy J. Harwood; Marco C. Knobloch; Andrew G. Lane; Aurélie Melgar; Joel D. Stohler; Clive R. Tuck; Helen C. Wheeler; Jürg A. Zarn; et al. (Crop Protection, 2026)

Divergent Selection on Dispersal Targets Chemosensory and Neuronal Genes in Tribolium castaneum - Michael D. Pointer; Will J. Nash; Lewis G. Spurgin; Mark McMullan; Simon Butler; David S. Richardson (Molecular Ecology, 2026)
Dispersal is key to the life history, ecology and evolution of many organisms and important in pest invasiveness. However, the genetic architecture underlying variation in dispersal behaviour remains poorly understood outside of a few model species. We investigated the genomic basis of dispersal using artificial selection on replicated lines of Tribolium castaneum , a flour beetle, an emergent model system and an economically important agricultural pest. Combining whole‐genome resequencing with population‐level genotype–phenotype association analysis, we identify nine genomic regions and 42 genes associated with selection on dispersal. Identified candidate genes were significantly enriched for functions related to neuronal structure and function, as well as chemosensory behaviour and mating, suggesting that variation in dispersal is mediated by neural and chemosensory pathways. Our results demonstrate that dispersal propensity has a polygenic basis and support an interaction between dispersal and mating ecology in this system. These findings contribute to a deeper understanding of the genetic mechanisms driving dispersal evolution and its role in shaping eco‐evolutionary dynamics.

Repeated barrier drown-out is required to facilitate long-distance migration of a potamodromous fish - Jason D. Thiem; Benjamin G. Fanson; David Ryan; Gavin L. Butler; David A. Crook; Doug J. Harding; Anthony Townsend; Ian J. Wooden; Ivor Stuart (Aquatic Sciences, 2025)
Migratory fish species are highly vulnerable to stream fragmentation. Potamodromous golden perch ( Macquaria ambigua ) inhabit the barrier-laden Murray–Darling Basin (MDB), Australia’s largest river system, and its lifecycle includes a requirement for uninterrupted stretches of flowing water habitat. Owing to these barriers, large-scale connectivity in many regions is limited to periods of high flow events that facilitate barrier drown-out. We undertook a 3-year (2021–2024) study using telemetry to quantify the movements of 150 adult golden perch from the Barwon–Darling River over a period that encompassed numerous high flow events and flooding. Approximately 75% of tagged golden perch undertook movements > 50 km, with > 90% of movements in an upstream direction, extending up to 1500 km and associated with increased river discharge. Tributary entries were detected on multiple occasions, with an apparent preference for specific tributaries. Ten fish migrated > 1000 km upstream across multiple flow events. The results of this study (1) highlight the importance of the Barwon–Darling River and tributaries as a key migration conduit for adult golden perch, (2) demonstrate that multiple flow events are required to achieve large-scale dispersal and (3) provide quantitative flow-movement relationships that can be used to support inter-regional management actions. These management actions might include barrier removal, the construction of fishways and protection of tributary–mainstem flow events.

Otolith and Genomic Data Reveal Temporal Insights Into Stocking Across a Large River Basin in a Mobile, Long‐Lived Australian Freshwater Fish Species - Katherine A. Harrisson; Luciano B. Beheregaray; Christopher M. Bice; Emily J. Booth; Chris J. Brauer; Gavin L. Butler; David Dawson; Olga Dudchenko; Benjamin G. Fanson; Graeme Hackett; Annique Harris; Matthew J. Jones; et al. (Molecular Ecology, 2025)
Freshwater ecosystems and their biota are under increasing pressure from anthropogenic stressors. In response to declining fish stocks, hatchery and stocking programmes are widely implemented as core components of restoration and management strategies, with positive outcomes for some wild populations. Despite this, stocking remains contentious due to potential genetic and ecological risks to wild populations. Monitoring and evaluation of stocking outcomes are critical to ensuring the long‐term sustainability of wild populations, but identification of stocked individuals post‐release remains a key challenge, particularly for mobile species. In this study, we combined otolith (natal origin and age) and genomic data to identify stocked individuals and evaluate the genetic implications of stocking for a culturally and socioeconomically important and mobile freshwater fish, golden perch Macquaria ambigua (family: Percichthyidae), across Australia's Murray–Darling Basin (MDB). We also generated a chromosome‐level genome assembly. Many close kin were detected across the MDB, increasing in prevalence over recent decades and mostly of hatchery origin. Rivers with many close kin were associated with low effective population sizes ( N e

Rationale and design of the Dog Aging Project precision cohort: a multi-omic resource for longitudinal research in geroscience - Jena Prescott; Amber J. Keyser; Paul Litwin; Matthew D. Dunbar; Robyn McClelland; Audrey Ruple; Holley Ernst; Brianna L. Butler; Mandy Kauffman; Anne Avery; Benjamin R. Harrison; Maria Partida-Aguilar; et al. (GeroScience, 2025)

Corrigendum to “Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes” [Biol. Conserv. 300 (2024), 110843] - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2025)

Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2024)

Traits Underlying Experimentally Evolved Dispersal Behavior in Tribolium castaneum - Michael D. Pointer; Lewis G. Spurgin; Ramakrishnan Vasudeva; Mark McMullan; Simon Butler; David S. Richardson (Journal of Insect Behavior, 2024)
Dispersal is an important behavior in many animals, with profound effects on individual fitness and the evolutionary trajectories of populations. This is especially true within taxa with particular life-history strategies, for example those that exploit ephemeral habitat. Further, dispersal is commonly seen to be part of behavioral syndromes - suites of traits that covary across behavioral contexts. The red flour beetle, Tribolium castaneum (Coleoptera, Tenebrionidae), is a major post-harvest crop pest responsible for large losses through the infestation of stored grain. In this system dispersal is known to have a strong genetic basis and differential artificial selection on dispersal traits produces strong phenotypic divergence. However, it is unknown which traits are able to rapidly evolve to produce these results, or which behavioral components underlie differences in dispersal. Using replicate lines of T. castaneum previously selected for divergent dispersal behavior, we test for correlated activity and movement patterns, morphology and substrate surface use. We find robustly repeatable associations between the dispersal phenotype and higher activity, straighter paths, larger body size (but not relative leg length) and increased tendency to remain at the surface of fodder. Together our results suggest that dispersal is part of a syndrome of traits in T. castaneum , and must be treated as such when considering the evolution of dispersal in this system, and in attempting to predict and control its spread.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Correlates of bird collisions with buildings across three North American countries - Jared A. Elmore; Stephen B. Hager; Bradley J. Cosentino; Timothy J. O'Connell; Corey S. Riding; Michelle L. Anderson; Marja H. Bakermans; Than J. Boves; David Brandes; Eric M. Butler; Michael W. Butler; Nicolette L. Cagle; et al. (Conservation Biology, 2021)
Collisions with buildings cause up to 1 billion bird fatalities annually in the United States and Canada. However, efforts to reduce collisions would benefit from studies conducted at large spatial scales across multiple study sites with standardized methods and consideration of species‐ and life‐history‐related variation and correlates of collisions. We addressed these research needs through coordinated collection of data on bird collisions with buildings at sites in the United States (35), Canada (3), and Mexico (2). We collected all carcasses and identified species. After removing records for unidentified carcasses, species lacking distribution‐wide population estimates, and species with distributions overlapping fewer than 10 sites, we retained 269 carcasses of 64 species for analysis. We estimated collision vulnerability for 40 bird species with ≥2 fatalities based on their North American population abundance, distribution overlap in study sites, and sampling effort. Of 10 species we identified as most vulnerable to collisions, some have been identified previously (e.g., Black‐throated Blue Warbler [ Setophaga caerulescens ]), whereas others emerged for the first time (e.g., White‐breasted Nuthatch [ Sitta carolinensis ]), possibly because we used a more standardized sampling approach than past studies. Building size and glass area were positively associated with number of collisions for 5 of 8 species with enough observations to analyze independently. Vegetation around buildings influenced collisions for only 1 of those 8 species (Swainson's Thrush [ Catharus ustulatus ]). Life history predicted collisions; numbers of collisions were greatest for migratory, insectivorous, and woodland‐inhabiting species. Our results provide new insight into the species most vulnerable to building collisions, making them potentially in greatest need of conservation attention to reduce collisions and into species‐ and life‐history‐related variation and correlates of building collisions, information that can help refine collision management.

Engineered biosynthesis of cyclotides - Thomas N. G. Handley; Hyon-Xhi Tan; Malcolm T. Rutledge; Hans Henning Brewitz; Joel D. A. Tyndall; Torsten Kleffmann; Margi I. Butler; Russell T. M. Poulter; Sigurd M. Wilbanks (New Zealand Journal of Botany, 2020)

Reconstruction of Atlantic herring ( Clupea harengus ) recruitment in the North Sea for the past 455 years based on the δ 13 C from annual shell increments of the ocean quahog ( Arctica islandica ) - Juan Estrella‐Martínez; Bernd R. Schöne; Ruth H. Thurstan; Elisa Capuzzo; James D. Scourse; Paul G. Butler (Fish and Fisheries, 2019)
Understanding the recruitment variability of the Atlantic herring North Sea stock remains a key objective of stock assessment and management. Although many efforts have been undertaken linking climatic and stock dynamic factors to herring recruitment, no major attempt has been made to estimate recruitment levels before the 20th century. Here, we present a novel annually resolved, absolutely dated herring recruitment reconstruction, derived from stable carbon isotope geochemistry (δ 13 C), from ocean quahog shells from the Fladen Ground (northern North Sea). Our age model is based on a growth increment chronology obtained from fourteen shells. Ten of these were micromilled at annual resolution for δ 13 C analysis. Our results indicate that the anthropogenically driven relative depletion of 13 C, the oceanic Suess effect ( oSE ), became evident in the northern North Sea in the 1850s. We calculated a regression line between the oSE ‐detrended δ 13 C results (δ 13 CṠ) and diatom abundance in the North Sea, the regression being mediated by the effect of phytoplankton on the δ 13 C of the ambient dissolved inorganic carbon. We used this regression to build an equation mediated by a nutritional link to reconstruct herring recruitment using δ 13 CṠ. The reconstruction suggests that there were five extended episodes of low‐recruitment levels before the 20th century. These results are supported by measured recruitment estimates and historical fish catch and export documentation. This work demonstrates that molluscan sclerochronological records can contribute to the investigation of ecological baselines and ecosystem functioning impacted by anthropogenic activity with implications for conservation and stock management.

Global biodiversity research tied up by juridical interpretations of access and benefit sharing - D. Neumann; A. V. Borisenko; J. A. Coddington; C. L. Häuser; C. R. Butler; A. Casino; J. C. Vogel; G. Haszprunar; P. Giere (Organisms Diversity & Evolution, 2018)

Evidence for different QTL underlying the immune and hypersensitive responses of Eucalyptus globulus to the rust pathogen Puccinia psidii - J. B. Butler; J. S. Freeman; R. E. Vaillancourt; B. M. Potts; M. Glen; D. J. Lee; G. S. Pegg (Tree Genetics & Genomes, 2016)

Testing the generality of above‐ground biomass allometry across plant functional types at the continent scale - Keryn I. Paul; Stephen H. Roxburgh; Jerome Chave; Jacqueline R. England; Ayalsew Zerihun; Alison Specht; Tom Lewis; Lauren T. Bennett; Thomas G. Baker; Mark A. Adams; Dan Huxtable; Kelvin D. Montagu; et al. (Global Change Biology, 2016)
Accurate ground‐based estimation of the carbon stored in terrestrial ecosystems is critical to quantifying the global carbon budget. Allometric models provide cost‐effective methods for biomass prediction. But do such models vary with ecoregion or plant functional type? We compiled 15 054 measurements of individual tree or shrub biomass from across Australia to examine the generality of allometric models for above‐ground biomass prediction. This provided a robust case study because Australia includes ecoregions ranging from arid shrublands to tropical rainforests, and has a rich history of biomass research, particularly in planted forests. Regardless of ecoregion, for five broad categories of plant functional type (shrubs; multistemmed trees; trees of the genus Eucalyptus and closely related genera; other trees of high wood density; and other trees of low wood density), relationships between biomass and stem diameter were generic. Simple power‐law models explained 84–95% of the variation in biomass, with little improvement in model performance when other plant variables (height, bole wood density), or site characteristics (climate, age, management) were included. Predictions of stand‐based biomass from allometric models of varying levels of generalization (species‐specific, plant functional type) were validated using whole‐plot harvest data from 17 contrasting stands (range: 9–356 Mg ha −1 ). Losses in efficiency of prediction were stand ‐level biomass prediction was 99%, with a mean absolute prediction error of only 13%. Hence, for cost‐effective prediction of biomass across a wide range of stands, we recommend use of generic allometric models based on plant functional types. Development of new species‐specific models is only warranted when gains in accuracy of stand‐based predictions are relatively high (e.g. high‐value monocultures).

Molecular and morphological insights into the origin of the invasive greater white-toothed shrew (Crocidura russula) in Ireland - Laura M. Gargan; Raphaël Cornette; Jon M. Yearsley; W. Ian Montgomery; Joana Paupério; Paulo C. Alves; Fidelma Butler; Michel Pascal; Anne Tresset; Anthony Herrel; John Lusby; David G. Tosh; et al. (Biological Invasions, 2016)

Trends in marine climate change research in the Nordic region since the first IPCC report - M. W. Pedersen; A. Kokkalis; H. Bardarson; S. Bonanomi; W. J. Boonstra; W. E. Butler; F. K. Diekert; N. Fouzai; M. Holma; R. E. Holt; K. Ø. Kvile; E. Nieminen; et al. (Climatic Change, 2016)

Age and growth of mangrove red snapper Lutjanus argentimaculatus at its cool‐water‐range limits - T. P. Piddocke; G. L. Butler; P. A. Butcher; J. Stewart; D. J. Bucher; L. Christidis (Journal of Fish Biology, 2015)
This study investigates the age and growth of Lutjanus argentimaculatus at its southern (cooler) range limits in eastern Australia. Specimens were collected from New South Wales and southern Queensland between November 2011 and December 2013. Fork lengths ( L F ) ranged from 190 to 1019 mm, and ages ranged from 2+ to 57+ years. Growth was described by the von Bertalanffy growth function with coefficients L ∞ = 874·92 mm, K = 0·087 year −1 and t 0 = −2·76 years. Estimates of the instantaneous natural mortality rate ( M ) ranged from 0·072 to 0·25. The L F (mm) and mass ( W ; g) relationship was represented by the equation: . The maximum age of 57+ years is the oldest reported for any lutjanid and comparisons with tropical studies suggest that the age‐based demography of L. argentimaculatus follows a latitudinal gradient. High maximum ages and low natural mortality rates indicate considerable vulnerability to overexploitation at the species' cool‐water‐range limits. These results demonstrate the need to identify underlying processes driving latitudinal gradients in fish demography.

Atlantic bluefin tuna Thunnus thynnus feeding ecology in the northern Gulf of Mexico: a preliminary description of diet from the western Atlantic spawning grounds - C. M. Butler; J. M. Logan; J. M. Provaznik; E. R. Hoffmayer; M. D. Staudinger; J. M. Quattro; M. A. Roberts; G. W. Ingram; A. G. Pollack; M. E. Lutcavage (Journal of Fish Biology, 2015)
A combination of stomach contents, nitrogen stable‐isotope and tissue C:N values are presented to demonstrate feeding activity of Atlantic bluefin tuna Thunnus thynnus on the Gulf of Mexico (GOMEX) spawning grounds. Diets include teleosts, cephalopods, crustaceans and a pelagic tunicate ( Pyrosoma atlanticum ). Results reveal the need to classify the GOMEX as a T. thynnus feeding ground.

Light brown apple moth (Epiphyas postvittana) (Lepidoptera: Tortricidae) colonization of California - D. M. Suckling; L. D. Stringer; D. B. Baird; R. C. Butler; T. E. S. Sullivan; D. R. Lance; G. S. Simmons (Biological Invasions, 2014)

Skeletal muscle adaptations to physical inactivity and subsequent retraining in young men - E. L. Campbell; O. R. Seynnes; R. Bottinelli; J. S. McPhee; P. J. Atherton; D. A. Jones; G. Butler-Browne; M. V. Narici (Biogerontology, 2013)

Invertebrate Community Patterns in Seasonal Ponds in Minnesota, USA: Response to Hydrologic and Environmental Variability - Matthew M. Bischof; Mark A. Hanson; Mark R. Fulton; Randy K. Kolka; Stephen D. Sebestyen; Malcolm G. Butler (Wetlands, 2013)

Genome-wide association study of glioma and meta-analysis - Preetha Rajaraman; Beatrice S. Melin; Zhaoming Wang; Roberta McKean-Cowdin; Dominique S. Michaud; Sophia S. Wang; Melissa Bondy; Richard Houlston; Robert B. Jenkins; Margaret Wrensch; Meredith Yeager; Anders Ahlbom; et al. (Human Genetics, 2012)

Microdeletion/microduplication of proximal 15q11.2 between BP1 and BP2: a susceptibility region for neurological dysfunction including developmental and language delay - Rachel D. Burnside; Romela Pasion; Fady M. Mikhail; Andrew J. Carroll; Nathaniel H. Robin; Erin L. Youngs; Inder K. Gadi; Elizabeth Keitges; Vikram L. Jaswaney; Peter R. Papenhausen; Venkateswara R. Potluri; Hiba Risheg; et al. (Human Genetics, 2011)

Leptidea sinapis (Wood White butterfly) egg-laying habitat and adult dispersal studies in Herefordshire - S. A. Clarke; D. G. Green; J. Joy; K. Wollen; I. Butler (Journal of Insect Conservation, 2011)

Evidence Supporting the use of Probiotics for the Prevention and Treatment of Chemotherapy-Induced Intestinal Mucositis - Luca D. Prisciandaro; Mark S. Geier; Ross N. Butler; Adrian G. Cummins; Gordon S. Howarth (Critical Reviews in Food Science and Nutrition, 2011)

Metallothionein Treatment Attenuates Microglial Activation and Expression of Neurotoxic Quinolinic Acid Following Traumatic Brain Injury - R. S. Chung; Y. K. Leung; C. W. Butler; Y. Chen; E. D. Eaton; M. W. Pankhurst; A. K. West; G. J. Guillemin (Neurotoxicity Research, 2009)

Structure and membrane affinity of new amphiphilic siderophores produced by Ochrobactrum sp. SP18 - Jessica D. Martin; Yusai Ito; Vanessa V. Homann; Margo G. Haygood; Alison Butler (JBIC Journal of Biological Inorganic Chemistry, 2006)

Biotic interactions as determinants of ecosystem structure in prairie wetlands: An example using fish - Mark A. Hanson; Kyle D. Zimmer; Malcolm G. Butler; Brian A. Tangen; Brian R. Herwig; Ned H. Euliss (Wetlands, 2005)

Investigating the Relationship Between Site-specific Yield and Protein of Cereal Crops - S. Norng; A. N. Pettitt; R. M. Kelly; D. G. Butler; W. M. Strong (Precision Agriculture, 2005)

Interspecies relationships, community structure, and factors influencing abundance of submerged macrophytes in prairie wetlands - Kyle D. Zimmer; Mark A. Hanson; Malcolm G. Butler (Wetlands, 2003)

Chemically-Enhanced Phytoextraction of Cadmium-Contaminated Soils Using Wheat (Triticum aestivumL.) - M. T. Begonia; G. B. Begonia; A. D. Butler; U. Griffin; C. Young (Bulletin of Environmental Contamination and Toxicology, 2003)

Selectivity for zooplankton prey by fathead minnows and brook sticklebacks - Leah M. Laurich; Kyle D. Zimmer; Malcolm G. Butler; Mark A. Hanson (Wetlands, 2003)

Comparative In Vitro Surveillance of Amoxicillin-Clavulanic Acid and Four Oral Comparators Against 21,232 Clinical Isolates from Europe - D. J. Hoban; S. K. Bouchillon; J. L. Johnson; G. G. Zhanel; D. L. Butler; K. A. Saunders; L. A. Miller; J. A. Poupard (European Journal of Clinical Microbiology & Infectious Diseases, 2003)

Comparative In Vitro Potency of Gemifloxacin and Fluoroquinolones Against Recent European Clinical Isolates from a Global Surveillance Study - D. Hoban; S. Bouchillon; J. Johnson; G. Zhanel; D. Butler; L. Miller; J. Poupard; the Gemifloxacin Surveillance Study Research Group (European Journal of Clinical Microbiology & Infectious Diseases, 2001)

Effects of rotenone on aquatic invertebrate communities in prairie wetlands - Christina L. Melaas; Kyle D. Zimmer; Malcolm G. Butler; Mark A. Hanson (Hydrobiologia, 2001)

Effects of Fathead Minnow Colonization and Removal on a Prairie Wetland Ecosystem - Kyle D. Zimmer; Mark A. Hanson; Malcolm G. Butler (Ecosystems, 2001)

A comparison of horizontally and vertically deployed aquatic invertebrate activity traps - Miles J. Muscha; Kyle D. Zimmer; Malcolm G. Butler; Mark A. Hanson (Wetlands, 2001)

Identification of genomic regions associated with stay green in sorghum by testing RILs in multiple environments - Y. Z. Tao; R. G. Henzell; D. R. Jordan; D. G. Butler; A. M. Kelly; C. L. McIntyre (Theoretical and Applied Genetics, 2000)

A surface-associated activity trap for capturing water-surface and aquatic invertebrates in wetlands - Mark A. Hanson; Christiane C. Roy; Ned H. Euliss; Kyle D. Zimmer; Michael R. Riggs; Malcolm G. Butler (Wetlands, 2000)

Osmoregulation in North American eels ( Anguilla rostrata LeSueur) on land and in freshwater: effects of the corpuscles of Stannius - D. G. Butler (Journal of Comparative Physiology B, 1999)

Regional distribution of metallothionein and zinc in the mouse gut - C. D. Tran; R. N. Butler; J. C. Philcox; A. M. Rofe; G. S. Howarth; P. Coyle (Biological Trace Element Research, 1998)

Corpuscles of Stannius and stanniocalcin-like immunoreactivity in the white sucker ( Catostomus commersoni ): evidence for a new cell-type - D. H. Zhang; G. Y. Oudit; L. E. Marra; D. G. Butler; J. H. Youson (Cell and Tissue Research, 1998)

Effects of ANG II and III and angiotensin receptor blockers on nasal salt gland secretion and arterial blood pressure in conscious Pekin ducks ( Anas platyrhynchos ) - D. G. Butler; R. Zandevakili; G. Y. Oudit (Journal of Comparative Physiology B, 1998)

Mapping of the gene encoding the B56β subunit of protein phosphatase 2A (PPP2R5B) to a 0.5-Mb region of chromosome 11q13 and its exclusion as a candidate gene for multiple endocrine neoplasia type 1 (MEN1) - S. A. Forbes; A. A. J. Pannett; J. H. D. Bassett; B. Harding; C. Wooding; R. V. Thakker; R. Butler; D. Ogilvie; R. Anand; P. Gaudray; G. Weber; C. Larsson; et al. (Human Genetics, 1997)

s of papers presented at the Forty-First annual meeting - R. E. Anderson; A. P. Benson; W. J. Hooker; Gerard S. Birth; Karl H. Norris; Reiner Bonde; Robert Akeley; Donald Merriam; C. C. Craft; H. W. Siegelman; W. L. Butler; L. A. Dionne; et al. (American Journal of Potato Research, 1958)